Oxygen storage material and method for producing the same

A pyrochlore type ceria-zirconia composite oxide with scandium and praseodymium or lanthanum enhances oxygen storage capacity (OSC) at low temperatures and maintains it after high-temperature exposure, addressing the limitations of conventional materials.

JP2024174489AActive Publication Date: 2024-12-17KK TOYOTA CHUO KENKYUSHO +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023092341
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-05
Publication Date
2024-12-17
Estimated Expiration
2043-06-05

AI Technical Summary

Technical Problem

Conventional oxygen storage materials, such as those described in Patent Documents 1 and 2, are not sufficient for meeting the increasing demands of exhaust gas purification catalysts, particularly in maintaining oxygen storage capacity (OSC) at both low temperatures and after exposure to high temperatures for extended periods.

Method used

A pyrochlore type ceria-zirconia composite oxide is developed by incorporating scandium and praseodymium or lanthanum, with specific atomic ratios and substitution of these elements into the ceria-zirconia lattice, followed by pressure molding and high-temperature reduction and oxidation treatments to enhance OSC.

Benefits of technology

The resulting oxygen storage material exhibits excellent OSC at 250°C and maintains this capacity even after exposure to high temperatures of about 1100°C for a long time, improving heat resistance and low-temperature performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024174489000005
    Figure 2024174489000005
  • Figure 2024174489000006
    Figure 2024174489000006
  • Figure 2024174489000007
    Figure 2024174489000007
Patent Text Reader

Abstract

To provide an oxygen storage material that can exhibit excellent oxygen storage capacity (OSC) at a low temperature around 250°C, both at the early stages of use and after long-term exposure to high-temperature exhaust gases at around 1,100°C.SOLUTION: An oxygen storage material contains a pyrochlore-type ceria (CeO2)-zirconia (ZrO2) composite oxide containing scandium (Sc) and praseodymium (Pr) or lanthanum (La). Relative to all cations in the pyrochlore-type ceria-zirconia composite oxide, a content of Ce is 43 to 49 at%, a content of Pr or La is 0.5 to 4.9 at%, a content of Sc is 0.5 to 4.9 at%, and an atomic ratio (Ce / Zr) of Ce and Zr is 45 / 55 to 51 / 49.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an oxygen storage material containing a pyrochlore-type ceria-zirconia composite oxide and a method for producing the same. [Background technology]

[0002] Three-way catalysts are known as exhaust gas purification catalysts that can oxidize carbon monoxide (CO) and hydrocarbons (HC) in exhaust gas emitted from internal combustion engines such as automobile engines, while simultaneously reducing nitrogen oxides (NOx).

[0003] In purifying exhaust gas using an exhaust gas purification catalyst, in order to absorb fluctuations in the oxygen concentration in the exhaust gas and increase the exhaust gas purification capacity, it is known to use a material with oxygen storage capacity (Oxygen Storage Capacity (OSC)) that can store oxygen when the oxygen concentration in the exhaust gas is high and release oxygen when the oxygen concentration in the exhaust gas is low as a support or co-catalyst for the exhaust gas purification catalyst.

[0004] As an oxygen storage material having such an OSC, ceria has conventionally been used suitably. In recent years, various types of composite oxides containing ceria have been researched, and various ceria-zirconia composite oxides obtained by the so-called coprecipitation method, reverse coprecipitation method, hydrothermal synthesis method, melting method, solid phase method, etc. have been developed.

[0005] For example, JP 2015-182931 A (Patent Document 1) discloses a method for producing a ceria-zirconia composite oxide that contains cerium, zirconium, and other transition metal elements such as iron, manganese, cobalt, nickel, and copper, and has a pyrochlore phase as a crystal structure, by a so-called melting method.

[0006] In addition, JP 2022-59284 A (Patent Document 2) describes an oxygen storage material containing a pyrochlore-type ceria-zirconia composite oxide and iron added to the pyrochlore-type ceria-zirconia composite oxide, in which the content ratio of Fe to the total amount of Ce and Zr (Fe / (Ce+Zr)×100) is 0.5 to 9 at%, the molar fraction of Zr to the total number of moles of Ce and Zr (X=Zr / (Ce+Zr)×100) is X=40 to 50%, and the lattice constant calculated from the X-ray diffraction pattern obtained by X-ray diffraction measurement using CuKα before and after heating at 1100° C. in air for 5 hours is expressed by the formula: lattice constant≦−7.00×10 -3 X+10.874, and the intensity ratio (I(14 / 29) value) between the diffraction line at 2θ=14.5° and the diffraction line at 2θ=29° obtained from the X-ray diffraction pattern obtained by X-ray diffraction measurement using CuKα before and after heating at 1100°C in air for 5 hours satisfies the formula: I(14 / 29) value≦2.36×10 -3 Oxygen storage materials are disclosed that meet the criteria represented by X-0.072.

[0007] However, in recent years, the required characteristics of exhaust gas purification catalysts have been increasing, and there is a demand for oxygen storage materials that can exhibit excellent oxygen storage capacity (OSC) at a low temperature of 250°C, not only at the initial stage of use but also after long-term exposure to high-temperature exhaust gases of about 1100°C. Conventional oxygen storage materials such as those described in Patent Documents 1 and 2 have not necessarily been sufficient. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2015-182931 A [Patent Document 2] Patent Publication No. 2022-59284 Summary of the Invention [Problem to be solved by the invention]

[0009] The present invention has been made in consideration of the problems associated with the above-mentioned conventional techniques, and aims to provide an oxygen storage material capable of exhibiting excellent oxygen storage capacity (OSC) at a low temperature of 250°C, not only in the initial stage of use but also after long-term exposure to high-temperature exhaust gases at approximately 1100°C, and a method for producing the same. [Means for solving the problem]

[0010] As a result of intensive research conducted by the present inventors in order to achieve the above object, it has been discovered that a scandium-containing ceria-zirconia solid solution powder is produced by using scandium and praseodymium or lanthanum in combination as elements to be added to a pyrochlore-type ceria-zirconia composite oxide, and adjusting the cerium content, the praseodymium or lanthanum content, the scandium content, and the atomic ratio of cerium to zirconium within predetermined ranges. The powder is then pressurized at a predetermined pressure to form a scandium-containing ceria-zirconia solid solution, which is then reduced under predetermined high-temperature conditions and then oxidized, thereby producing a high-temperature powder having a temperature of about 1100° C. The inventors have found that a composite oxide in which scandium and praseodymium or lanthanum are sufficiently dissolved in a pyrochlore-type ceria-zirconia composite oxide can be obtained both before and after exposure to exhaust gas for a long period of time, and that this pyrochlore-type ceria-zirconia composite oxide containing scandium and praseodymium or lanthanum can exhibit excellent oxygen storage capacity (OSC) at a low temperature of 250°C not only in the initial stage of use but also after exposure to high-temperature exhaust gas of about 1100°C for a long period of time, thereby completing the present invention.

[0011] That is, the present invention provides the following aspects.

[0012] [1] A pyrochlore-type ceria (CeO2)-zirconia (ZrO2) composite oxide containing scandium (Sc) and praseodymium (Pr) or lanthanum (La), With respect to all cations in the pyrochlore-type ceria-zirconia composite oxide, The Ce content is 43 to 49 at%. The content of Pr or La is 0.5 to 4.9 at %, The Sc content is 0.5 to 4.9 at%; An oxygen storage material having an atomic ratio of Ce to Zr (Ce / Zr) of 45 / 55 to 51 / 49.

[0013] [2] The oxygen storage material according to [1], wherein at least a portion of Sc and Pr or La is dissolved in the pyrochlore-type ceria-zirconia composite oxide.

[0014] [3] The oxygen storage material according to [1] or [2], wherein at least a portion of Sc is substituted at a Zr site in the pyrochlore-type ceria-zirconia composite oxide, and at least a portion of Pr or La is substituted at a Ce site in the pyrochlore-type ceria-zirconia composite oxide.

[0015] [4] The Sc distribution map, Pr or La distribution map, Ce distribution map, and zero-mean normalized correlation coefficient (ZNCC) values ​​calculated based on the Sc distribution map in the element mapping image obtained by energy dispersive X-ray analysis, [Sc-Zr], [Sc-Ce], [M PL -Ce] and [M PL -Zr] is represented by the following formulas (1) and (2): [Sc-Zr]-[Sc-Ce]>0.000 (1) [M PL -Ce]-[M PL -Zr]>0.028 (2) (In the above formula, [Sc-Zr] represents the ZNCC coefficient value between the Sc distribution map and the Zr distribution map, [Sc-Ce] represents the ZNCC coefficient value between the Sc distribution map and the Ce distribution map, and [M PL -Ce] represents the ZNCC coefficient value between the Pr or La distribution map and the Ce distribution map, and [M PL -Zr] represents the ZNCC coefficient value between the Pr or La distribution map and the Zr distribution map.) The oxygen storage material according to any one of [1] to [3], which satisfies the condition represented by the following formula:

[0016] [5] A method for producing an oxygen storage material containing a pyrochlore-type ceria (CeO2)-zirconia (ZrO2)-based composite oxide containing scandium (Sc) and praseodymium (Pr) or lanthanum (La), comprising the steps of: preparing a ceria-zirconia-based solid solution powder containing scandium and praseodymium or lanthanum, the Ce content being 43-49 at%, the Pr or La content being 0.5-4.9 at%, the Sc content being 0.5-4.9 at%, and the atomic ratio of Ce to Zr (Ce / Zr) being 45 / 55-51 / 49, relative to all cations; a step of compressing and molding the ceria-zirconia solid solution powder containing scandium and praseodymium or lanthanum at a pressure of 30 to 350 MPa, reducing the powder at a temperature of 1400 to 2000°C, and then oxidizing the powder to obtain an oxygen storage material containing the pyrochlore-type ceria-zirconia composite oxide containing scandium and praseodymium or lanthanum according to claim 1; A method for producing an oxygen storage material comprising:

[0017] The reason why the oxygen storage material of the present invention can exhibit excellent OSC at a low temperature of 250°C not only in the initial stage of use but also after long-term exposure to high-temperature exhaust gases at about 1100°C is not entirely clear, but the inventors speculate as follows. That is, the superlattice structure of CeO2-ZrO2 in the pyrochlore-type ceria-zirconia composite oxide containing scandium and praseodymium or lanthanum that constitutes the oxygen storage material of the present invention undergoes a phase change between the pyrochlore phase (Ce2Zr2O7) and the κ phase (Ce2Zr2O8) depending on the oxygen partial pressure in the gas phase, and exhibits OSC. Sc 3+ The ionic radius of Zr 4+ Since the ionic radius of Sc is close to that of Zr in the pyrochlore-type ceria-zirconia composite oxide containing scandium and praseodymium or lanthanum according to the present invention, it is believed that Sc ions selectively substitute for Zr sites. When Zr sites are substituted with Sc ions, it is presumed that the superlattice structure containing oxygen defects generated by charge compensation is more stabilized while ensuring heat resistance.3+ Or La 3+ The ionic radius of Ce 3+ Since the ionic radius of the Pr ion or La ion is close to that of the Pr ion, it is considered that the Pr ion or La ion selectively substitutes for the Ce site in the pyrochlore-type ceria-zirconia composite oxide containing scandium and praseodymium or lanthanum according to the present invention. When the Ce site is substituted with the Pr ion or La ion, it is presumed that the deterioration of the pyrochlore structure is suppressed even when the material is exposed to high-temperature exhaust gas of about 1100°C for a long period of time. For these reasons, it is presumed that the oxygen storage material of the present invention can exhibit an excellent OSC at a low temperature of 250°C even after being exposed to high-temperature exhaust gas of about 1100°C for a long period of time. Effect of the Invention

[0018] According to the present invention, it is possible to obtain an oxygen storage material that can exhibit excellent oxygen storage capacity (OSC) at a low temperature of 250°C, not only at the initial stage of use but also after long-term exposure to high-temperature exhaust gas at about 1100°C. [Brief description of the drawings]

[0019] [Figure 1] FIG. 1 is a distribution diagram of the elements Ce, Zr, Pr, and Sc in the composite oxide powder obtained in Example 5 before the heat resistance test. [Diagram 2] FIG. 2 is a distribution diagram of the elements Ce, Zr, Pr, and Sc in the composite oxide powder obtained in Comparative Example 3 before the heat resistance test. [Diagram 3] 1 is a graph showing the results of plotting the difference ([Sc-Zr]-[Sc-Ce]) in ZNCC coefficient values ​​of the composite oxide powders obtained in Examples 1 to 7 and Comparative Examples 1 to 4, and 7 to 8 before heat resistance testing against the Sc content. [Figure 4] 1 is a graph showing the results of plotting the difference ([MPL-Ce]-[MPL-Zr]) in ZNCC coefficient values ​​of the composite oxide powders before heat resistance testing obtained in Examples 1 to 7 and Comparative Examples 1 to 4 and 6 against the Pr or La content. [Diagram 5]1 is a graph showing the results of plotting the oxygen storage capacity (OSC) of catalyst powders in which platinum is supported on composite oxide powders after heat resistance testing obtained in Examples 1 to 7 and Comparative Examples 1 to 8 against the Sc content. [Figure 6] 1 is a graph showing the results of plotting the oxygen storage capacity (OSC) of catalyst powders in which platinum is supported on the composite oxide powders after heat resistance testing obtained in Examples 1 to 7 and Comparative Examples 1 to 8 against the Pr or La content. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] The present invention will be described in detail below based on preferred embodiments thereof.

[0021] First, the oxygen storage material of the present invention will be described. The oxygen storage material of the present invention contains a pyrochlore-type ceria (CeO2)-zirconia (ZrO2) composite oxide containing scandium (Sc) and praseodymium (Pr) or lanthanum (La), With respect to all cations in the pyrochlore-type ceria-zirconia composite oxide, The Ce content is 43 to 49 at%. The content of Pr or La is 0.5 to 4.9 at %, The Sc content is 0.5 to 4.9 at%; The atomic ratio of Ce to Zr (Ce / Zr) is 45 / 55 to 51 / 49.

[0022] The oxygen storage material of the present invention contains a ceria-zirconia composite oxide having a superlattice structure in which Ce and Zr are regularly arranged (hereinafter referred to as "pyrochlore-type ceria-zirconia composite oxide"). The oxygen storage material containing such a pyrochlore-type ceria-zirconia composite oxide has a higher oxygen diffusion rate in the bulk than a ceria-zirconia composite oxide having a fluorite structure, and therefore has excellent oxygen storage capacity (OSC). Note that by recognizing the presence of a peak (peak appearing at 2θ=14.0° to 16.0°) derived from the superlattice structure in an X-ray diffraction measurement using CuKα rays, it can be confirmed that the ceria-zirconia composite oxide is a pyrochlore type having a superlattice structure.

[0023] In the oxygen storage material of the present invention, the Ce content relative to all cations in the pyrochlore-type ceria-zirconia composite oxide must be 43 to 49 at%, preferably 44 to 49 at%, and more preferably 46 to 49 at%. If the Ce content is below the lower limit, the OSC capacity that can be expressed decreases, while if the Ce content exceeds the upper limit, CeO2 undergoes phase separation when exposed to high temperatures, causing the superlattice structure to collapse and decreasing the OSC.

[0024] In the oxygen storage material of the present invention, the Pr or La content must be 0.5 to 4.9 at% and preferably 1.0 to 2.5 at% based on all cations in the pyrochlore-type ceria-zirconia composite oxide. If the Pr or La content is below the lower limit, the heat resistance decreases, whereas if the Pr or La content exceeds the upper limit, the OSC at low temperatures decreases.

[0025] Furthermore, in the oxygen storage material of the present invention, the Sc content must be 0.5 to 4.9 at% relative to all cations in the pyrochlore-type ceria-zirconia composite oxide, and is preferably 1.0 to 2.5 at%. If the Sc content is below the lower limit, the effect of improving the OSC at low temperatures decreases, while if the Sc content exceeds the upper limit, the heat resistance decreases.

[0026] In the oxygen storage material of the present invention, the atomic ratio of Ce to Zr (Ce / Zr) must be 45 / 55 to 51 / 49, and is preferably 46 / 54 to 50 / 50. If Ce / Zr is below the lower limit, the OSC capacity that can be expressed decreases, while if Ce / Zr exceeds the upper limit, CeO2 undergoes phase separation when exposed to high temperatures, causing the superlattice structure to collapse and decreasing the OSC.

[0027] Furthermore, in the oxygen storage material of the present invention, it is preferable that at least a part of Sc and Pr or La is solid-solved in the pyrochlore-type ceria-zirconia composite oxide, and it is more preferable that at least a part of Sc is substituted at the Zr site in the pyrochlore-type ceria-zirconia composite oxide, and at least a part of Pr or La is substituted at the Ce site in the pyrochlore-type ceria-zirconia composite oxide. This improves the heat resistance and OSC at low temperatures. On the other hand, if Sc and Pr or La are not solid-solved in the pyrochlore-type ceria-zirconia composite oxide, if Sc is not substituted at the Zr site in the pyrochlore-type ceria-zirconia composite oxide, or if Pr or La is not substituted at the Ce site in the pyrochlore-type ceria-zirconia composite oxide, the heat resistance and OSC at low temperatures are not sufficiently improved.

[0028] In addition, even if Sc and Pr or La are added to the pyrochlore-type ceria-zirconia composite oxide, the so-called solid-phase synthesis method Impregnation In the case of methods such as the above, it is difficult to sufficiently dissolve Sc and Pr or La in a pyrochlore-type ceria-zirconia composite oxide, and therefore the addition of Sc and Pr or La does not contribute to improving the heat resistance and OSC at low temperatures. In contrast, in the present invention, by the production method of the present invention described below, it is possible to obtain a pyrochlore-type ceria-zirconia composite oxide in which Sc and Pr or La are sufficiently dissolved, which was not possible to obtain in the past, and it is possible to achieve improvements in the heat resistance and the OSC at low temperatures.

[0029] In addition, in the oxygen storage material of the present invention, the coefficient values ​​[Sc-Zr], [Sc-Ce], and [M] of zero-means normalized cross-correlation (ZNCC) calculated based on a Sc distribution map, a Pr or La distribution map, and a Ce distribution map in an element mapping image (EDX element mapping image) obtained by energy dispersive X-ray analysis (EDX), are PL -Ce] and [M PL -Zr] is represented by the following formulas (1) and (2): [Sc-Zr]-[Sc-Ce]>0.000 (1) [M PL -Ce]-[M PL -Zr]>0.028 (2) (In the above formula, [Sc-Zr] represents the ZNCC coefficient value between the Sc distribution map and the Zr distribution map, [Sc-Ce] represents the ZNCC coefficient value between the Sc distribution map and the Ce distribution map, and [M PL -Ce] represents the ZNCC coefficient value between the Pr or La distribution map and the Ce distribution map, and [M PL -Zr] represents the ZNCC coefficient value between the Pr or La distribution map and the Zr distribution map.) It is preferable to satisfy the condition expressed by the following formula: PL -Ce]-[M PL In an oxygen storage material in which [—Zr] satisfies the conditions represented by the above formulas (1) and (2), Sc is sufficiently substituted at the Zr site and Pr or La is sufficiently substituted at the Ce site, and therefore the material has excellent heat resistance and OSC at low temperatures.

[0030] The EDX element mapping image was obtained, for example, using a scanning transmission electron microscope equipped with an energy dispersive X-ray analyzer, with a field magnification of 4.8×10 7 This can be obtained by performing EDX analysis under twice the conditions.

[0031] In addition, the ZNCC coefficient values ​​[Sc-Zr], [Sc-Ce], and [M PL -Ce] and [M PL-Zr] is calculated based on the comparative image (the Sc, Pr or La distribution map) and the reference image (the Ce or Zr distribution map) in the EDX element mapping image by the following formula (3):

[0032]

number

[0033] (where ZNCC represents the coefficient value of the zero-mean normalized cross-correlation (ZNCC), I(i,j) represents the luminance value of the ith pixel in the horizontal direction and the jth pixel in the vertical direction in the comparison image (the Sc, Pr or La distribution map), and I ave represents the average luminance value in the comparison image, T(i,j) represents the luminance value of the i-th pixel in the horizontal direction and the j-th pixel in the vertical direction in the reference image (the Ce or Zr distribution map), and T ave represents the average luminance value in the reference image. Specifically, the ZNCC coefficient values ​​of the comparison image (the Sc, Pr, or La distribution map) and the reference image (the Ce or Zr distribution map) can be calculated using image processing software ImageJ or Matlab.

[0034] The ZNCC coefficient value thus obtained is ZNCC=1.0 when the comparison image (the Sc, Pr or La distribution map) and the reference image (the Ce or Zr distribution map) completely match, and ZNCC=-1.0 when they completely contradict each other. For example, when the Sc distribution map and the Zr distribution map are compared and Sc is present in the Zr site (i.e., the Zr site is substituted with Sc), the ZNCC coefficient value [Sc-Zr] is positive and is 1.0 or less.

[0035] In the oxygen storage material of the present invention, the ceria-zirconia composite oxide is a pyrochlore type, and the cationic sites in the crystal lattice are divided into Zr sites and Ce sites. When Sc is dissolved in such a pyrochlore type ceria-zirconia composite oxide and Sc is substituted at the Zr site, the ZNCC coefficient value [Sc-Zr] is positive. When Sc is not present at the Ce site, the ZNCC coefficient value [Sc-Ce] is negative. Therefore, the difference in the ZNCC coefficient value ([Sc-Zr]-[Sc-Ce]) can be used as an index showing whether Sc is selectively substituted at the Zr site, and the larger [Sc-Zr]-[Sc-Ce] means that Sc is selectively substituted at the Zr site. Similarly, when Pr or La is dissolved in the pyrochlore type ceria-zirconia composite oxide and Pr or La is substituted at the Ce site, the ZNCC coefficient value [M PL -Ce] is positive. In addition, when Pr or La is not present at the Zr site, the ZNCC coefficient value [M PL -Zr] is negative. Therefore, the difference in the ZNCC coefficient values ​​([M PL -Ce]-[M PL -Zr]) can be used as an indicator of whether Pr or La is selectively substituted at the Ce site, and M PL -Ce]-[M PL -Zr] is larger, it means that Pr or La is selectively substituted for the Ce site.

[0036] Therefore, in the oxygen storage material of the present invention, Sc is selectively substituted at the Zr site, and Pr or La is selectively substituted at the Ce site. From the viewpoint of further improving the heat resistance and the OSC at low temperatures, the ZNCC coefficient values ​​[Sc-Zr], [Sc-Ce], and [M PL -Ce] and [M PL -Zr] is represented by the following formulas (1A) and (2A): [Sc-Zr]-[Sc-Ce]>0.010 (1A) [M PL -Ce]-[M PL -Zr]>0.100 (2A) It is preferable that the condition represented by the following formulas (1B) and (2B): [Sc-Zr]-[Sc-Ce]>0.020 (1B) [M PL -Ce]-[M PL -Zr]>0.120 (2B) It is more preferable that the condition expressed by the following formula (1) is satisfied.

[0037] The average crystallite diameter of the oxygen storage material of the present invention is preferably 0.1 to 10 μm, more preferably 0.2 to 5 μm. If the average crystallite diameter of the oxygen storage material is less than the lower limit, the superlattice structure tends to be difficult to maintain after long-term exposure to high-temperature exhaust gas of about 1100 ° C., while if it exceeds the upper limit, the OSC improvement effect tends to be difficult to obtain sufficiently. Note that such an average crystallite diameter can be calculated based on the Scherrer formula using a commercially available analysis software (for example, "JADE" manufactured by Materials Data Corporation) using the half-width of the diffraction line near 2θ = 29 ° obtained from the X-ray diffraction pattern obtained by X-ray diffraction measurement using CuKα.

[0038] The specific surface area of ​​the oxygen storage material of the present invention is not particularly limited, but is preferably 0.01 to 20 m 2 / g, and 0.05 to 10 m 2 / g is more preferable, and 0.1 to 5m 2 / g is even more preferable. If the specific surface area of ​​the oxygen storage material is less than the lower limit, the oxygen storage capacity tends to be small, while if it exceeds the upper limit, the number of particles with small particle diameters increases, and the heat resistance tends to decrease. Note that such a specific surface area can be calculated as a BET specific surface area from the adsorption isotherm using the BET isothermal adsorption equation.

[0039] Furthermore, the oxygen storage material of the present invention may further contain at least one element selected from the group consisting of rare earth elements other than cerium, scandium, praseodymium and lanthanum and alkaline earth elements. By containing such an element, when the oxygen storage material of the present invention is used as a carrier for an exhaust gas purification catalyst, a higher exhaust gas purification ability tends to be exhibited. Such rare earth elements other than cerium, scandium, praseodymium and lanthanum include yttrium (Y), neodymium (Nd), samarium (Sm), gadolinium (Gd), terbium (Tb), dysprosium (Dy), ytterbium (Yb), lutetium (Lu), etc., and among them, Nd and Y are preferred from the viewpoint of tending to stabilize the superlattice structure. In addition, examples of alkaline earth metal elements include magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), and radium (Ra). Among these, Mg, Ca, and Ba are preferred from the viewpoint of their tendency to stabilize the superlattice structure.

[0040] In the case where at least one element selected from the group consisting of rare earth elements other than cerium, scandium, praseodymium, and lanthanum and alkaline earth elements is further contained, the content of said element is preferably 0.5 to 20 at%, and more preferably 1 to 10 at%, based on all cations in the pyrochlore-type ceria-zirconia composite oxide. If the content of such an element is less than the lower limit, the effect of stabilizing the superlattice structure tends to decrease, while if it exceeds the upper limit, the oxygen storage capacity tends to decrease.

[0041] The oxygen storage material of the present invention contains the pyrochlore-type ceria-zirconia composite oxide and scandium and praseodymium or lanthanum added to the pyrochlore-type ceria-zirconia composite oxide, and is capable of exhibiting an excellent OSC at a low temperature of 250°C, not only at the beginning of use but also after long-term exposure to high-temperature exhaust gas of about 1100°C. Therefore, the oxygen storage material of the present invention is suitably used as a support or co-catalyst for exhaust gas purification catalysts. A suitable example of the oxygen storage material of the present invention is an exhaust gas purification catalyst consisting of a support made of the oxygen storage material of the present invention and a precious metal supported on the support. Examples of such precious metals include platinum, rhodium, palladium, osmium, iridium, gold, silver, etc. Another example is one in which the oxygen storage material of the present invention is arranged around an exhaust gas purification catalyst in which a precious metal is supported on other catalyst support fine particles.

[0042] Next, a method for producing the oxygen storage material of the present invention will be described. The method for producing the oxygen storage material of the present invention is a method for producing an oxygen storage material containing a pyrochlore-type ceria (CeO2)-zirconia (ZrO2)-based composite oxide containing scandium (Sc) and praseodymium (Pr) or lanthanum (La), A step (first step) of preparing a ceria-zirconia solid solution powder containing scandium and praseodymium or lanthanum, the Ce content being 43 to 49 at%, the Pr or La content being 0.5 to 4.9 at%, the Sc content being 0.5 to 4.9 at%, and the atomic ratio of Ce to Zr (Ce / Zr) being 45 / 55 to 51 / 49, relative to all cations; a step (second step) of compressing and molding the ceria-zirconia solid solution powder containing scandium and praseodymium or lanthanum at a pressure of 30 to 350 MPa, reducing the powder at a temperature of 1400 to 2000°C, and then oxidizing the powder to obtain an oxygen storage material containing the pyrochlore-type ceria-zirconia composite oxide containing scandium and praseodymium or lanthanum according to claim 1; The method includes:

[0043] First, in a first step, a ceria-zirconia solid solution powder is prepared, which contains scandium (Sc) and praseodymium (Pr) or lanthanum (La), and has a Ce content of 43 to 49 at% (preferably 44 to 49 at%, more preferably 46 to 49 at%), a Pr or La content of 0.5 to 4.9 at% (preferably 1.0 to 2.5 at%), a Sc content of 0.5 to 4.9 at% (preferably 1.0 to 2.5 at%), and an atomic ratio of Ce to Zr (Ce / Zr) of 45 / 55 to 51 / 49 (preferably 46 / 54 to 50 / 50) relative to all cations.

[0044] In the ceria-zirconia solid solution powder containing scandium and praseodymium or lanthanum, if the Ce content is less than the lower limit, the OSC capacity that can be expressed is reduced, and on the other hand, if the Ce content exceeds the upper limit, when exposed to high temperatures, CeO2 undergoes phase separation, the superlattice structure collapses, and the OSC is reduced. In addition, in the ceria-zirconia solid solution powder containing scandium and praseodymium or lanthanum, if the Pr or La content is less than the lower limit, the heat resistance is reduced, and on the other hand, if the Pr or La content exceeds the upper limit, the OSC at low temperatures is reduced. Furthermore, in the ceria-zirconia solid solution powder containing scandium and praseodymium or lanthanum, if the Sc content is less than the lower limit, the effect of improving the OSC at low temperatures is reduced, and on the other hand, if the Sc content exceeds the upper limit, the heat resistance is reduced. Furthermore, if the Ce / Zr ratio is less than the lower limit, the OSC capacity that can be expressed decreases, whereas if the Ce / Zr ratio exceeds the upper limit, CeO2 undergoes phase separation when exposed to high temperatures, the superlattice structure collapses, and the OSC capacity decreases.

[0045] In addition, in the ceria-zirconia solid solution powder containing scandium and praseodymium or lanthanum, it is preferable to use a solid solution in which ceria and zirconia are mixed at the atomic level, from the viewpoint of more fully forming a superlattice structure. Moreover, the ceria-zirconia solid solution powder containing scandium and praseodymium or lanthanum preferably has an average primary particle size of about 2 to 100 nm, more preferably about 5 to 70 nm, and further preferably has a specific surface area of ​​1.0 to 100 m. 2 / g, and 10 to 80m 2 / g is more preferable, and 30 to 80m 2 It is even more preferred that the .mu.m / g.

[0046] The method for preparing (preparing) such a ceria-zirconia solid solution powder containing scandium and praseodymium or lanthanum is not particularly limited, and examples thereof include a method of producing the solid solution powder by adopting a so-called coprecipitation method so that the content ratio of cerium, zirconium, scandium, and praseodymium or lanthanum is within the above range. Examples of such coprecipitation methods include a method of using an aqueous solution containing a cerium salt (e.g., nitrate), a zirconium salt (e.g., nitrate), a scandium salt (e.g., nitrate), a praseodymium salt (e.g., nitrate), or a lanthanum salt (e.g., nitrate) to generate a coprecipitate in the presence of ammonia, centrifuging and washing the obtained coprecipitate, drying it, and further calcining it, and then pulverizing it using a pulverizer such as a ball mill to obtain the ceria-zirconia solid solution powder containing scandium and praseodymium or lanthanum. The aqueous solution containing the cerium salt, the zirconium salt, the scandium salt, and the praseodymium salt or the lanthanum salt is prepared so that the content ratios of cerium, zirconium, scandium, and praseodymium or lanthanum in the obtained solid solution powder are within predetermined ranges.

[0047] In addition, the aqueous solution containing the cerium salt, the zirconium salt, the scandium salt, and the praseodymium salt or the lanthanum salt may contain, as necessary, a salt of at least one element selected from the group consisting of cerium, scandium, and rare earth elements other than praseodymium or lanthanum, and alkaline earth elements, a surfactant (e.g., a nonionic surfactant), etc. By incorporating at least one element selected from the group consisting of cerium, scandium, and rare earth elements other than praseodymium or lanthanum, and alkaline earth elements, into the ceria-zirconia solid solution powder containing scandium and praseodymium or lanthanum, when the oxygen storage material of the present invention is used as a co-catalyst for an exhaust gas purification catalyst, a higher exhaust gas purification ability tends to be exhibited. Examples of rare earth elements other than cerium, scandium, and praseodymium or lanthanum include yttrium (Y), neodymium (Nd), samarium (Sm), gadolinium (Gd), terbium (Tb), dysprosium (Dy), ytterbium (Yb), and lutetium (Lu), among which, Nd and Y are preferred from the viewpoint of tending to stabilize the superlattice structure. Examples of alkaline earth metal elements include magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), and radium (Ra), among which, Mg, Ca, and Ba are preferred from the viewpoint of tending to stabilize the superlattice structure.

[0048] In the case where at least one element selected from the group consisting of cerium, scandium, and rare earth elements other than praseodymium or lanthanum and alkaline earth elements is further contained, the content of the element is preferably 0.5 to 20 at%, more preferably 1 to 10 at%, based on the total cations in the ceria-zirconia solid solution powder containing scandium and praseodymium or lanthanum. If the content of such an element is less than the lower limit, it tends to be difficult to stabilize the superlattice structure, while if it exceeds the upper limit, the oxygen storage capacity tends to decrease.

[0049] Next, in the second step, the ceria-zirconia solid solution powder containing scandium and praseodymium or lanthanum is pressure-molded at a pressure of 30 to 350 MPa (preferably, a pressure of 40 to 300 MPa). If the pressure-molding pressure is less than the lower limit, the contact between the secondary particles of the powder is not improved, so that the crystal growth during the reduction treatment is not sufficiently promoted, and the stability of the superlattice structure when exposed to high-temperature exhaust gas of about 1100°C for a long period of time is reduced. On the other hand, if the pressure-molding pressure exceeds the upper limit, the crystal growth during the reduction treatment proceeds too much, and the OSC at a low temperature of 250°C tends to decrease. The method of such pressure-molding is not particularly limited, and a known pressure-molding method such as a hydrostatic press can be appropriately adopted.

[0050] Next, in the second step, the pressure-molded solid solution powder compact is subjected to a reduction treatment in which the compact is heated under reducing conditions at a temperature of 1400 to 2000°C (preferably 1600 to 1900°C) for 0.5 to 24 hours (preferably 1 to 10 hours), and then subjected to an oxidation treatment to obtain the oxygen storage material powder of the present invention. If the temperature of the reduction treatment is below the lower limit, crystal growth does not proceed sufficiently, and the stability of the superlattice structure decreases. On the other hand, if the temperature of the reduction treatment exceeds the upper limit, the balance between the energy (e.g., power) required for the reduction treatment and the improvement of performance becomes poor. In addition, if the heating time during the reduction treatment is below the lower limit, the superlattice structure tends to be difficult to form sufficiently, and on the other hand, if the heating time exceeds the upper limit, the balance between the energy (e.g., power) required for the reduction treatment and the improvement of performance becomes poor.

[0051] The method of the reduction treatment is not particularly limited as long as it is a method that can heat-treat the solid solution powder under a reducing atmosphere under a predetermined temperature condition, and examples thereof include (i) a method in which the solid solution powder is placed in a vacuum heating furnace, evacuated, and then a reducing gas is introduced into the furnace to create a reducing atmosphere in the furnace and heated under a predetermined temperature condition to perform the reduction treatment; (ii) a method in which the solid solution powder is placed in a graphite furnace, evacuated, and then heated under a predetermined temperature condition to create a reducing atmosphere in the furnace by reducing gases such as CO and HC generated from the furnace body, heating fuel, etc., to perform the reduction treatment; and (iii) a method in which the solid solution powder is placed in a crucible filled with activated carbon, and then heated under a predetermined temperature condition to create a reducing atmosphere in the crucible by reducing gases such as CO and HC generated from the activated carbon, etc., to perform the reduction treatment.

[0052] The reducing gas used to achieve such a reducing atmosphere is not particularly limited, and reducing gases such as CO, HC, H2, and other hydrocarbon gases can be appropriately used. Among such reducing gases, it is more preferable to use one that does not contain carbon (C) from the viewpoint of preventing the generation of by-products such as zirconium carbide (ZrC) when performing a reducing treatment at a higher temperature. When such a reducing gas that does not contain carbon (C) is used, the reduction treatment can be performed at a higher temperature condition close to the melting point of zirconium, etc., and therefore the structural stability of the crystal phase can be sufficiently improved.

[0053] Furthermore, in the second step, an oxidation treatment is further carried out after the reduction treatment. By carrying out such an oxidation treatment, oxygen lost during reduction is compensated for in the obtained ceria-zirconia-based composite oxide containing scandium and praseodymium or lanthanum, and the stability as an oxide is improved. The method of such an oxidation treatment is not particularly limited, and for example, a method of heat treating the ceria-zirconia-based composite oxide containing scandium and praseodymium or lanthanum in an oxidizing atmosphere (for example, in air) can be suitably adopted. In addition, the heating temperature condition in such an oxidation treatment is not particularly limited, but is preferably about 300 to 800°C. Furthermore, the heating time in the oxidation treatment is not particularly limited, but is preferably about 0.5 to 5 hours.

[0054] In the second step, it is preferable to further subject the ceria-zirconia composite oxide containing scandium and praseodymium or lanthanum to a pulverization treatment after the reduction treatment and / or the oxidation treatment. The method of such a pulverization treatment is not particularly limited, and for example, a wet pulverization method, a dry pulverization method, a freeze pulverization method, etc. can be suitably adopted. EXAMPLES

[0055] The present invention will be described in more detail below based on examples and comparative examples, but the present invention is not limited to the following examples.

[0056] Example 1 First, 218.77g of cerium nitrate aqueous solution with a concentration of 28% by mass in terms of CeO2, 281.54g of zirconium nitrate aqueous solution with a concentration of 18% by mass in terms of ZrO2, an aqueous solution in which 6.1g of scandium nitrate tetrahydrate was dissolved in 100ml of pure water, and an aqueous solution in which 8.7g of praseodymium nitrate hexahydrate was dissolved in 100ml of pure water were mixed, and the resulting mixed solution was added to a solution in which 162.2g of 25% ammonia water was diluted with 450ml of pure water, and a coprecipitate was generated by stirring at 1000 rpm for 10 minutes using a homogenizer (manufactured by AS ONE Corporation). The resulting coprecipitate was dried in the air at 150°C for 7 hours using a degreasing furnace, and then calcined in the air at 400°C for 5 hours to obtain a ceria-zirconia solid solution containing scandium and praseodymium (Sc-Pr-containing ceria-zirconia solid solution). The solid solution was then pulverized using a pulverizer (AzOne Corporation's "Wonder Blender") to a particle size of 75 μm or less by sieving, to obtain a Sc-Pr-containing ceria-zirconia solid solution powder having an atomic ratio ([Ce]:[Zr]:[Pr]:[Sc]) of cerium, zirconium, praseodymium, and scandium of 43.5:51.5:2.5:2.5. In this Sc-Pr-containing ceria-zirconia solid solution powder, the atomic ratio (Ce / Zr) of Ce to Zr is 45.8 / 54.2.

[0057] Next, 20 g of this Sc-Pr-containing ceria-zirconia solid solution powder was packed into a polyethylene bag (volume 0.05 L), and after the inside was degassed, the mouth of the bag was heated and sealed. Then, a hydrostatic press ("CK4-22-60" manufactured by Nikkiso Co., Ltd.) was used to apply 3000 kgf / cm to the bag. 2 The powder was subjected to cold isostatic pressing (CIP) at a pressure (molding pressure) of 294 MPa for 1 minute to obtain a molded body of the Sc-Pr-containing ceria-zirconia solid solution powder. The size of the molded body was 20 mm in length, 20 mm in width, and 3 mm in average thickness.

[0058] The obtained molded body was then placed in a small vacuum pressure sintering furnace (FVPS-R-150 manufactured by Fuji Denpa Kogyo Co., Ltd.) and replaced with an argon atmosphere. Thereafter, the furnace was heated to 1000°C over a heating time of 1 hour, then heated to 1500°C (reduction treatment temperature) over a heating time of 4 hours and held at that temperature for 5 hours. After that, the furnace was cooled to 1000°C over a cooling time of 4 hours, and then allowed to cool naturally to room temperature to obtain a reduction-treated product.

[0059] The resulting reduction product was heated in air at 500°C for 5 hours to obtain a ceria-zirconia composite oxide containing scandium and praseodymium (Sc-Pr-containing ceria-zirconia composite oxide). The Sc-Pr-containing ceria-zirconia composite oxide was pulverized using the pulverizer so that the particle size was 75μm or less to obtain a Sc-Pr-containing ceria-zirconia composite oxide powder having an atomic ratio ([Ce]:[Zr]:[Pr]:[Sc]) of cerium, zirconium, praseodymium, and scandium of 43.5:51.5:2.5:2.5. In this Sc-Pr-containing ceria-zirconia composite oxide powder, the atomic ratio (Ce / Zr) of Ce to Zr was 45.8 / 54.2.

[0060] Example 2 Except for changing the amount of the cerium nitrate aqueous solution to 218.69 g and the amount of the praseodymium nitrate hexahydrate to 5.2 g, a Sc-Pr-containing ceria-zirconia composite oxide powder was obtained in which the atomic ratio ([Ce]:[Zr]:[Pr]:[Sc]) of the contents of cerium, zirconium, praseodymium, and scandium was 44.5:51.5:1.5:2.5. In this Sc-Pr-containing ceria-zirconia composite oxide powder, the atomic ratio (Ce / Zr) of Ce to Zr was 46.4 / 53.6.

[0061] Example 3 Except for changing the amount of the cerium nitrate aqueous solution to 238.35 g, the amount of the zirconium nitrate aqueous solution to 259.67 g, and the amount of the praseodymium nitrate hexahydrate to 5.22 g, the same procedure as in Example 1 was followed to obtain a Sc-Pr-containing ceria-zirconia composite oxide powder having an atomic ratio ([Ce]:[Zr]:[Pr]:[Sc]) of cerium, zirconium, praseodymium, and scandium of 48.5:47.5:1.5:2.5. In this Sc-Pr-containing ceria-zirconia composite oxide powder, the atomic ratio (Ce / Zr) of Ce to Zr is 50.5 / 49.5.

[0062] Example 4 An Sc-Pr-containing ceria-zirconia composite oxide powder having an atomic ratio ([Ce]:[Zr]:[Pr]:[Sc]) of cerium, zirconium, praseodymium, and scandium was obtained in the same manner as in Example 1, except that the amount of the zirconium nitrate aqueous solution was changed to 289.74 g, the amount of the scandium nitrate tetrahydrate was changed to 2.4 g, and the reduction treatment temperature was changed to 1700° C. In this Sc-Pr-containing ceria-zirconia composite oxide powder, the atomic ratio (Ce / Zr) of Ce to Zr was 45.1 / 54.9.

[0063] Example 5 The amount of the cerium nitrate aqueous solution was changed to 218.69 g, the amount of the zirconium nitrate aqueous solution was changed to 289.47 g, the amount of the scandium nitrate tetrahydrate was changed to 2.4 g, the amount of the praseodymium nitrate hexahydrate was changed to 5.2 g, and the reduction treatment temperature was changed to 1700° C. In the same manner as in Example 1, a Sc-Pr-containing ceria-zirconia composite oxide powder was obtained in which the content ratio of cerium, zirconium, praseodymium, and scandium was 44.5:45.0:1.5:1.0 in atomic ratio ([Ce]:[Zr]:[Pr]:[Sc]). In this Sc-Pr-containing ceria-zirconia composite oxide powder, the atomic ratio of Ce to Zr (Ce / Zr) was 45.6 / 54.4.

[0064] Example 6 A ceria-zirconia composite oxide powder containing scandium and lanthanum (Sc-La-containing ceria-zirconia composite oxide powder) having an atomic ratio ([Ce]:[Zr]:[La]:[Sc]) of cerium, zirconium, lanthanum, and scandium was 43.5:51.5:2.5:2.5 was obtained in the same manner as in Example 1, except that 8.7 g of lanthanum nitrate hexahydrate was used instead of the praseodymium nitrate hexahydrate and the heating temperature of the reduction treatment product was changed to 900° C. In this Sc-La-containing ceria-zirconia composite oxide powder, the atomic ratio (Ce / Zr) of Ce to Zr was 45.8 / 54.2.

[0065] Example 7 A ceria-zirconia composite oxide powder containing scandium and lanthanum (Sc-La-containing ceria-zirconia composite oxide powder) having a cerium, zirconium, lanthanum, and scandium content ratio of 47.5:47.5:2.5:2.5 in atomic ratio ([Ce]:[Zr]:[La]:[Sc]) was obtained in the same manner as in Example 1, except that 8.7 g of lanthanum nitrate hexahydrate was used instead of the praseodymium nitrate hexahydrate, the amount of the cerium nitrate aqueous solution was changed to 233.43 g, and the amount of the zirconium nitrate aqueous solution was changed to 259.67 g. In this Sc-La-containing ceria-zirconia composite oxide powder, the atomic ratio of Ce to Zr (Ce / Zr) was 50.0 / 50.0.

[0066] Comparative Example 1 The amount of the cerium nitrate aqueous solution was changed to 201.49 g, the amount of the zirconium nitrate aqueous solution was changed to 267.87 g, the amount of the scandium nitrate tetrahydrate was changed to 12.1 g, the amount of the praseodymium nitrate hexahydrate was changed to 17.4 g, and the reduction treatment temperature was changed to 1700° C. In the same manner as in Example 1, a Sc—Pr-containing ceria-zirconia composite oxide powder was obtained in which the content ratio of cerium, zirconium, praseodymium, and scandium was 41.0:49.0:5.0:5.0 in atomic ratio ([Ce]:[Zr]:[Pr]:[Sc]). In this Sc—Pr-containing ceria-zirconia composite oxide powder, the atomic ratio of Ce to Zr (Ce / Zr) was 45.6 / 54.4.

[0067] Comparative Example 2 The amount of the cerium nitrate aqueous solution was changed to 176.92 g, the amount of the zirconium nitrate aqueous solution was changed to 240.54 g, the amount of the scandium nitrate tetrahydrate was changed to 24.3 g, the amount of the praseodymium nitrate hexahydrate was changed to 34.8 g, and the reduction treatment temperature was changed to 1700° C. In the same manner as in Example 1, a Sc—Pr-containing ceria-zirconia composite oxide powder was obtained in which the content ratio of cerium, zirconium, praseodymium, and scandium was 36.0:44.0:10.0:10.0 in atomic ratio ([Ce]:[Zr]:[Pr]:[Sc]). In this Sc—Pr-containing ceria-zirconia composite oxide powder, the atomic ratio of Ce to Zr (Ce / Zr) was 45.0 / 55.0.

[0068] Comparative Example 3 First, a ceria-zirconia composite oxide powder having a cerium to zirconium content ratio of 46.0:54.0 in atomic ratio ([Ce]:[Zr]) was obtained in the same manner as in Example 1, except that the amount of the cerium nitrate aqueous solution was changed to 226.06 g, the amount of the zirconium nitrate aqueous solution was changed to 295.20 g, the scandium nitrate tetrahydrate and the praseodymium nitrate hexahydrate were not used, and the reduction treatment temperature was changed to 1700°C.

[0069] Next, the ceria-zirconia composite oxide powder was immersed in an aqueous solution containing scandium nitrate and praseodymium nitrate in a mass ratio of 1:1 to impregnate the ceria-zirconia composite oxide powder with scandium nitrate and praseodymium nitrate so that the scandium content was 5.0 at% and the praseodymium content was 5.0 at%. The solid components were then evaporated to dryness, and the powder was heated in air at 900°C for 5 hours to obtain a Sc-Pr-containing ceria-zirconia composite oxide powder having an atomic ratio ([Ce]:[Zr]:[Pr]:[Sc]) of cerium, zirconium, praseodymium, and scandium of 41.4:48.6:5.0:5.0. In the Sc-Pr-containing ceria-zirconia composite oxide powder, the atomic ratio (Ce / Zr) of Ce to Zr was 46.0 / 54.0.

[0070] Comparative Example 4 The ceria-zirconia composite oxide powder was impregnated with scandium nitrate and praseodymium nitrate so that the scandium content was 10.0 at% and the praseodymium content was 10.0 at% in the same manner as in Comparative Example 3, to obtain a Sc-Pr-containing ceria-zirconia composite oxide powder having an atomic ratio ([Ce]:[Zr]:[Pr]:[Sc]) of 36.8:43.2:10.0:10.0 of cerium, zirconium, praseodymium and scandium. In this Sc-Pr-containing ceria-zirconia composite oxide powder, the atomic ratio (Ce / Zr) of Ce and Zr was 46.0 / 54.0.

[0071] Comparative Example 5 A ceria-zirconia composite oxide powder having a cerium to zirconium content ratio of 50.0:50.0 in atomic ratio ([Ce]:[Zr]) was obtained in the same manner as in Example 1, except that the amount of the cerium nitrate aqueous solution was changed to 245.72 g, the amount of the zirconium nitrate aqueous solution was changed to 273.34 g, the scandium nitrate tetrahydrate and the praseodymium nitrate hexahydrate were not used, and the reduction treatment temperature was changed to 1700°C.

[0072] Comparative Example 6 A praseodymium-containing ceria-zirconia composite oxide powder (Pr-containing ceria-zirconia composite oxide powder) having an atomic ratio ([Ce]:[Zr]:[Pr]) of cerium, zirconium, and praseodymium was obtained in the same manner as in Example 1, except that the amount of the zirconium nitrate aqueous solution was changed to 295.20 g and the scandium nitrate tetrahydrate was not used. In this Pr-containing ceria-zirconia composite oxide powder, the atomic ratio (Ce / Zr) of Ce to Zr was 44.6 / 55.4.

[0073] Comparative Example 7 A ceria-zirconia composite oxide powder containing scandium (Sc-containing ceria-zirconia composite oxide powder) having a cerium:zirconium:sc content ratio ([Ce]:[Zr]:[Sc]) of 46.0:51.5:2.5 was obtained in the same manner as in Example 1, except that the amount of the cerium nitrate aqueous solution was changed to 226.06 g, the amount of the zirconium nitrate aqueous solution was changed to 281.54 g, and the praseodymium nitrate hexahydrate was not used. In this Sc-containing ceria-zirconia composite oxide powder, the atomic ratio of Ce to Zr (Ce / Zr) was 47.2 / 52.8.

[0074] Comparative Example 8 A Sc-containing ceria-zirconia composite oxide powder having an atomic ratio ([Ce]:[Zr]:[Sc]) of cerium, zirconium and scandium was 46.0:49.0:5.0 was obtained in the same manner as in Example 1, except that the amount of the cerium nitrate aqueous solution was changed to 226.06 g, the amount of the zirconium nitrate aqueous solution was changed to 267.87 g, the amount of the scandium nitrate tetrahydrate was changed to 12.1 g, the praseodymium nitrate hexahydrate was not used, and the reduction treatment temperature was changed to 1700° C. In this Sc-containing ceria-zirconia composite oxide powder, the atomic ratio (Ce / Zr) of Ce and Zr was 48.4 / 51.6.

[0075] <Heat resistance test 1> The composite oxide powders obtained in the examples and comparative examples were heated in air at 1100° C. for 5 hours.

[0076] <Heat resistance test 2> 1.5 g of the composite oxide powder obtained in the examples and comparative examples was heated at 1050°C for 5 hours while passing a rich gas (H2 (2%) + CO2 (10%) + H2O (3%) + N2 (balance)) and a lean gas (O2 (2%) + CO2 (10%) + H2O (3%) + N2 (balance)) alternately every 5 minutes at a gas flow rate of 500 ml / min.

[0077] <Energy dispersive X-ray analysis> The composite oxide powders obtained in the examples and comparative examples before the heat resistance test were thinned to about 500 nm by FIB (Focused Ion Beam) processing to prepare samples for observation. The samples for observation were observed using a spherical aberration corrected scanning transmission electron microscope ("JEM-ARM200F NEOARM" manufactured by JEOL Ltd.) equipped with an energy dispersive X-ray analyzer, with an acceleration voltage of 200 kV and a field of view magnification of 4.8 × 10 7 Energy dispersive X-ray (EDX) analysis was performed under conditions of 100x1000 and 100x200 to obtain an EDX element mapping image of 512 pixels vertical x 512 pixels horizontal, and a distribution map of each element of Ce, Zr, Pr or La and Sc was obtained. Figures 1 and 2 show the distribution maps of each element of Ce, Zr, Pr, and Sc of the composite oxide powders obtained in Example 5 and Comparative Example 3 before the heat resistance test, respectively.

[0078] <Zero Mean Normalized Correlation Coefficient (ZNCC)> Based on the distribution diagram of each element of Ce, Zr, Pr, or La, Sc obtained by the EDX analysis, the following formula (3):

[0079]

number

[0080] (where ZNCC represents the coefficient value of the zero-mean normalized cross-correlation (ZNCC), I(i,j) represents the luminance value of the ith pixel in the horizontal direction and the jth pixel in the vertical direction in the comparison image (the Sc, Pr or La distribution map (M=512, N=512)), and I ave represents the average luminance value in the comparison image, T(i,j) represents the luminance value of the i-th pixel in the horizontal direction and the j-th pixel in the vertical direction in the reference image (the Ce or Zr distribution map (M=512, N=512)), and T ave represents the average luminance value in the reference image. The ZNCC coefficient value [Sc-Ce] between the Sc distribution map and the Ce distribution map, the ZNCC coefficient value [Sc-Zr] between the Sc distribution map and the Zr distribution map, the ZNCC coefficient value [M PL-Ce], the ZNCC coefficient value [M of the Pr or La distribution diagram and the Zr distribution diagram PL -[Zr] was determined. Specifically, the ZNCC coefficient values of the comparison image (the Sc, Pr or La distribution diagram) and the reference image (the Ce or Zr distribution diagram) were calculated using the image processing software ImageJ. The results are shown in Table 1.

[0081]

Table 1

[0082] Also, based on the results shown in Table 1, the difference between the ZNCC coefficient value [Sc-Zr] and the ZNCC coefficient value [Sc-Ce] ([Sc-Zr]-[Sc-Ce]) and the ZNCC coefficient value [M PL -Ce] and the ZNCC coefficient value [M PL -Zr] difference ([M PL -Ce]-[M PL -Zr]) was determined. The results are shown in Table 2.

[0083] <X-ray diffraction (XRD) measurement> The X-ray diffraction patterns of each composite oxide powder before and after the heat resistance test obtained in the examples and comparative examples were measured using an X-ray diffractometer ("RINT-Ultima" manufactured by Rigaku Corporation) with CuKα rays as the X-ray source under the conditions of a tube voltage of 40 KV, a tube current of 40 mA, and a scanning speed of 2θ = 10° / min.

[0084] In the obtained X-ray diffraction pattern, the ratio of the peak intensity I(14) of the diffraction line near 2θ = 14.5° to the peak intensity I(29) of the diffraction line near 2θ = 29° [I(14 / 29) = I(14) / I(29)] was determined. Also, the following formula: Structure maintenance rate = I(14 / 29) after heat resistance test 1 / I(14 / 29) before heat resistance test × 100 was used to determine the structure maintenance rate. These results are shown in Table 2.

[0085] <Catalyst preparation> Each of the composite oxide powders obtained in the Examples and Comparative Examples before the heat resistance test and after heat resistance test 1 (Comparative Examples 1, 2, and 4) or after heat resistance test 2 (Examples 1 to 7 and Comparative Examples 3, 5 to 8) was impregnated with a dinitrodiammineplatinum(II) acid solution, evaporated to dryness, and further calcined at 300°C for 3 hours to prepare a catalyst powder in which platinum (Pt) was supported on the composite oxide powder (Pt loading: 1% by mass).

[0086] <Oxygen release measurement> 15 mg of each catalyst powder prepared as described above was placed in a thermogravimetric analyzer (Shimadzu Corporation, "TGA-50"), and a reducing gas (H2 (5%) + N2 (balance)) and an oxidizing gas (O2 (5%) + N2 (balance)) were passed through the catalyst powder at a temperature of 250°C alternately every 5 minutes at a gas flow rate of 100 ml / min, and the increase or decrease in the mass of the catalyst powder during this period was measured. The average mass loss of the catalyst powder during the second and third passes of the reducing gas was calculated and used as the oxygen storage capacity (OSC). The results are shown in Table 2.

[0087] [Table 2]

[0088] From the I(14 / 29) values ​​shown in Table 2, it was confirmed that the composite oxide powders obtained in the Examples and Comparative Examples were pyrochlore-type ceria-zirconia composite oxide powders.

[0089] Based on the results shown in Table 2, the difference in ZNCC coefficient value ([Sc-Zr]-[Sc-Ce]) was plotted against the Sc content in Figure 3. The difference in ZNCC coefficient value ([M PL -Ce]-[M PLThe results of plotting [Zr-Zr] against the Pr or La content are shown in Fig. 4. The straight line in Fig. 3 is based on the ZNCC coefficient value of the Sc-Pr-containing ceria-zirconia composite oxide powder (Comparative Example 3) prepared under conditions where Sc is hardly dissolved in the crystal lattice, and is a straight line indicating the boundary whether Sc is substituted at the Zr site or not. The straight line in Fig. 4 is based on the ZNCC coefficient value of the Sc-Pr-containing ceria-zirconia composite oxide powder prepared under conditions where Pr is hardly dissolved in the crystal lattice in Comparative Example 3, and is a straight line indicating the boundary whether Pr or La is substituted at the Ce site or not.

[0090] Furthermore, based on the results shown in Table 2, the oxygen storage capacity (OSC) of the catalyst powder in which platinum (Pt) is supported on the composite oxide powder after the heat resistance test is plotted against the Sc content and the Pr or La content, and the results are shown in Figures 5 and 6.

[0091] As shown in FIG. 3 and FIG. 4, the composite oxide powders obtained in Examples 1 to 7 and Comparative Examples 1, 2, and 4 had a difference in ZNCC coefficient value of [Sc-Zr]-[Sc-Ce]>0.000 and [M PL -Ce]-[M PL -Zr]>0.028, it was confirmed that Sc was dissolved in the ceria-zirconia crystal lattice and substituted for the Zr site, and Pr or La was dissolved in the ceria-zirconia crystal lattice and substituted for the Ce site. PL -Ce]-[M PL It was confirmed that Pr was dissolved in the ceria-zirconia crystal lattice and substituted at the Ce site, because the difference in ZNCC coefficient value of the composite oxide powders obtained in Comparative Examples 7 and 8 satisfied [Sc-Zr]-[Sc-Ce]>0.000, which confirmed that Sc was dissolved in the ceria-zirconia crystal lattice and substituted at the Zr site.

[0092] 5 and 6, it was found that the composite oxide powders obtained in Examples 1 to 7 have superior OSC compared to the composite oxide powders obtained in Comparative Examples 1 to 8. This is because the composite oxides obtained in Examples 1 to 6 have Sc 3+ Zr 4+ By replacing with Ce, the oxygen vacancies generated by charge compensation improve the mobility of the oxygen lattice, and the ionic radius becomes Ce 4+ (0.97Å) or larger 3+ (1.16Å) or La 3+ (1.13Å) is Ce 4+ This is believed to be because, in addition to the introduction of oxygen vacancies caused by the charge compensation described above, Pr2Zr2O7 or La2Zr2O7, which has high thermal stability, is partially formed by the substitution of La2Zr2O7, improving the heat resistance of the composite oxide powder and the low-temperature OSC after the heat resistance test.

[0093] On the other hand, in the composite oxide powders obtained in Comparative Examples 1 and 2, Sc is substituted at the Zr site and Pr or La is substituted at the Ce site, as in the composite oxides obtained in Examples 1 to 7. However, since the Sc content and Pr or La content are 5 at % or more, the structure becomes unstable and the change in the lattice during the oxidation-reduction of Ce is suppressed, which is considered to result in a decrease in OSC compared to the composite oxides obtained in Examples 1 to 7. The reason for this is not entirely clear, but the present inventors speculate as follows. That is, in the ceria-zirconia crystal lattice, Zr sites (Zr 4+ ) does not change its valence during the redox reaction and contributes greatly to the structural stability of the composite oxide powder during the redox reaction. However, in composite oxide powders with Sc and Pr or La contents of 5 at% or more, Zr 4+ Excessive Sc 3+ When substituted with Ce, excess oxygen vacancies are generated near the Zr site due to charge compensation, making the structure unstable. 4+ Excessive Pr 3+ Or La 3+By replacing with , Pr2Zr2O7 or La2Zr2O7 is generated in excess as a structural anchor, and the change in the lattice during the oxidation and reduction of Ce is suppressed. For these reasons, it is presumed that the low-temperature OSC after the heat resistance test decreased.

[0094] Furthermore, in the composite oxide powder obtained in Comparative Example 3, Sc and Pr were hardly dissolved in the ceria-zirconia crystal lattice, and therefore the substitution effect of Sc and Pr was not sufficiently obtained, which is considered to have resulted in a decrease in OSC compared to the composite oxides obtained in Examples 1 to 7.

[0095] Furthermore, in the composite oxide powder obtained in Comparative Example 4, Sc is substituted at the Zr site, and Pr or La is substituted at the Ce site, as in the composite oxides obtained in Examples 1 to 7. 4+ The content of Pr or La, which has a large ionic radius, is 10 at%. This leads to an increase in the ionic radius. 4+ From Ce 3+ It is considered that the OSC was decreased compared to the composite oxides obtained in Examples 1 to 7 because the reduction to 0 was inhibited.

[0096] Furthermore, the composite oxide powders obtained in Comparative Examples 5 to 8 did not contain Sc and at least one of Pr and La, and therefore the substitution effects of Sc and Pr or La could not be obtained simultaneously. This is believed to have resulted in a decrease in OSC compared to the composite oxides obtained in Examples 1 to 7. [Industrial Applicability]

[0097] As described above, according to the present invention, it is possible to obtain an oxygen storage material that can exhibit excellent oxygen storage capacity (OSC) at a low temperature of about 250° C., not only at the beginning of use but also after long-term exposure to exhaust gas at a high temperature of about 1100° C. Therefore, since the oxygen storage material of the present invention has both excellent oxygen storage capacity (OSC) at low temperatures and high-temperature durability, it is useful as a support or co-catalyst for exhaust gas purification catalysts, a catalyst atmosphere adjuster, etc.

Claims

1. Pyrochlore-type ceria (CeO 2 )-zirconia (ZrO 2 )-based composite oxide, With respect to all cations in the pyrochlore-type ceria-zirconia composite oxide, The Ce content is 43 to 49 at %, The content of Pr or La is 0.5 to 4.9 at %, The Sc content is 0.5 to 4.9 at%; The atomic ratio of Ce to Zr (Ce / Zr) is 45 / 55 to 51 / 49; 1. An oxygen storage material comprising:

2. 2. The oxygen storage material according to claim 1, wherein at least a part of Sc and Pr or La is dissolved in the pyrochlore-type ceria-zirconia composite oxide.

3. 2. The oxygen storage material according to claim 1, wherein at least a portion of Sc substitutes for a Zr site in the pyrochlore-type ceria-zirconia composite oxide, and at least a portion of Pr or La substitutes for a Ce site in the pyrochlore-type ceria-zirconia composite oxide.

4. The Sc distribution map, Pr or La distribution map, Ce distribution map, and zero-mean normalized correlation coefficient (ZNCC) values ​​[Sc-Zr], [Sc-Ce], and [M PL -Ce] and [M PL -Zr] is represented by the following formulas (1) and (2): [Sc-Zr]-[Sc-Ce]>0.000 (1) [M PL -Ce]-[M PL -Zr]>0.028 (2) (In the above formula, [Sc-Zr] represents the ZNCC coefficient value between the Sc distribution map and the Zr distribution map, [Sc-Ce] represents the ZNCC coefficient value between the Sc distribution map and the Ce distribution map, and [M PL -Ce] represents the ZNCC coefficient value of the Pr or La distribution map and the Ce distribution map, and [M PL -Zr] represents the ZNCC coefficient value of the Pr or La distribution map and the Zr distribution map.) 2. The oxygen storage material according to claim 1, wherein the oxygen storage material satisfies the condition expressed by:

5. Pyrochlore-type ceria (CeO 2 )-zirconia (ZrO 2 A method for producing an oxygen storage material containing an O 2 O 3 based composite oxide, comprising the steps of: A step of preparing a ceria-zirconia-based solid solution powder containing scandium and praseodymium or lanthanum, the Ce content being 43 to 49 at%, the Pr or La content being 0.5 to 4.9 at%, the Sc content being 0.5 to 4.9 at%, and the atomic ratio of Ce to Zr (Ce / Zr) being 45 / 55 to 51 / 49, relative to all cations; a step of compressing and molding the ceria-zirconia solid solution powder containing scandium and praseodymium or lanthanum at a pressure of 30 to 350 MPa, reducing the powder at a temperature of 1400 to 2000° C., and then oxidizing the powder to obtain an oxygen storage material containing the pyrochlore-type ceria-zirconia composite oxide containing scandium and praseodymium or lanthanum according to claim 1; A method for producing an oxygen storage material, comprising:

Citation Information

Patent Citations

  • Cerium-zirconium type complex oxide and production method thereof

    JP2015182931A

  • Oxygen storage material and method for producing the same

    JP2020059630A

  • Oxygen storage material and production method thereof

    JP2022059284A